Global materials versus local materials for students’ reading comprehension: a library research - Heri Kurniawan (UPT Bahasa Universitas Tanjungpura, 2020)
This study scientifically aimed to investigate whether or not local materials influences reading comprehension towards students in general instructional settings, compared to global materials. The researcher conducted the study by collecting 20 empirical research articles from 2009 till 2018 through computer searches from the database and through book readings, related to global and local materials and experimental studies for investigating the effectiveness between the global and the local materials towards learner's reading comprehension. As soon as the researcher gathered the articles, the articles were then analyzed and synthesized into data results and discussion related to the theories. The researcher also consulted data result and consultation with the experts of the English Language Teaching Materials. The result had synthetically shown that the local materials, integrated local culture content inside were more active compared by the global materials for reading comprehension because of students' background knowledge of their local cultural familiarity in the target language materials. It also emphasized the strong influence of the usage of it for students' reading comprehension improvement.